Potential of the nematode Steinernema sp. for the biological control of the Andean weevil - GARZÓN-C., MARTÍN YESID; AZA-T., BEIMAR OCTAVIO; JIMÉNEZ-G., JAIME; LUQUE-Z., JESÚS E. (Revista Colombiana de Entomología, 1996)
The Andean weevil Premnotrypes vorax (Hustache) is an important pest of the Colombian potato crops. Nevertheless its importance, few research has been carried out looking for alternatives of control different to the chemical. Based on previous reports, a soil entomopathogenic nematode was isolated and identified from Colombian potatoes fields in Villapinzón, Cundinamarca. Its pathogenicity to the weevil was compared with that of the product EXHIBIT, which active principle is Steinernema carpocapsae strain 25. The new nematode was multiplied in vivo in Gallería mellonella (L). larvae, following Dukty’s procedures, and it belongs to the genus Steinernema, and seems to be a new species. By casing bioassays the median lethal concentration (LC,0) to the weevil was established, being 526,43 and 26,30 nematodes /ml for the native nematode and S. carpocapsae, respectively, indicating that S. carpocapsae strain 25 is 20 times more pathogenic to P vorax than the native nematode.